Spike It, Mo! - Adler, David A.; Ricks, Sam (New York : Penguin Young Readers, an imprint of Penguin Random House LLC, 2022)
"Mo and his dad play volleyball for the first time while enjoying a day at the beach! Can Mo win the final point for his team, or will the sun get in his way?"--Back cover.
Junior Library Guild
Ages 6-8.
Grades 1-3.
A Junior Library Guild selection
Keywords: Fathers and sons -- Juvenile fiction; Readers (Primary); Volleyball -- Juvenile fiction; Fathers and sons -- Fiction; Readers; Volleyball -- Fiction; Easy reading materials; Father-son relationship -- Fiction; Volleyball -- Fiction; Readers (Primary)